General practitioner practice-based pharmacist input to medicines optimisation in the UK: pragmatic, multicenter, randomised, controlled trial - Nadia Farhanah Syafhan; Sayer Al Azzam; Steven D. Williams; Wendy Wilson; Jayne Brady; Peter Lawrence; Mark McCrudden; Mustafa Ahmed; Michael G. Scott; Glenda Fleming; Anita Hogg; Claire Scullin; et al. (Journal of Pharmaceutical Policy and Practice, 2021)
Background Changing demographics across the UK has led to general practitioners (GPs) managing increasing numbers of older patients with multi-morbidity and resultant polypharmacy. Through government led initiatives within the National Health Service, an increasing number of GP practices employ pharmacist support. The purpose of this study is to evaluate the impact of a medicines optimisation intervention, delivered by GP practice-based pharmacists, to patients at risk of medication-related problems (MRPs), on patient outcomes and healthcare costs. Methods A multi-centre, randomised (normal care or pharmacist supplemented care) study in four regions of the UK, involving patients (n = 356) from eight GP practices, with a 6-month follow-up period. Participants were adult patients who were at risk of MRPs. Results Median number of MRPs per intervention patient were reduced at the third assessment, i.e. 3 to 0.5 (p < 0.001) in patients who received the full intervention schedule. Medication Appropriateness Index (MAI) scores were reduced (medications more appropriate) for the intervention group, but not for control group patients (8 [4–13] to 5 [0–11] vs 8 [3–13] to 7 [3–12], respectively; p = 0.001). Using the intention-to-treat (ITT) approach, the number of telephone consultations in intervention group patients was reduced and different from the control group (1 [0–3] to 1 [0–2] vs 1 [0–2] to 1 [0–3], p = 0.020). No significant differences between groups were, however, found in unplanned hospital admissions, length of hospital stay, number of A&E attendances or outpatient visits. The mean overall healthcare cost per intervention patient fell from £1041.7 ± 1446.7 to £859.1 ± 1235.2 (p = 0.032). Cost utility analysis showed an incremental cost per patient of − £229.0 (95% CI − 594.6, 128.2) and a mean QALY gained of 0.024 (95% CI − 0.021 to 0.065), i.e. indicative of a health status gain at a reduced cost (2016/2017). Conclusion The pharmacist service was effective in reducing MRPs, inappropriateness of medications and telephone consultations in general practice in a cost-effective manner. Trial registration: ClinicalTrials.Gov, NCT03241498. Registered 7 August 2017—Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03241498